Unipodal stance influences radiographic evaluation of foot balance in horses. Issue 3 (12th March 2019) - Joostens, Zoë; Evrard, Laurence; Busoni, Valeria
Abstract: Lifting the contralateral forelimb (unipodal stance) is often used as a method of restraint in horses. This experimental one group pretest, posttest study was conducted to evaluate the effects of unipodal stance on quantitative radiographic parameters in equine forefeet. Seven nonlame horses were randomly selected. Lateromedial (LM) and dorsopalmar (DP) projections were acquired for both forefeet, squarely placed on blocks, using two X‐ray generators. Radiographs of each foot were acquired first in a bipodal stance, immediately followed by the same radiographic projections obtained in a unipodal stance. The following measurements were recorded for each stance: distal interphalangeal joint (DIPJ) space width on both projections; mediolateral joint balance as the difference between lateral and medial DIPJ space widths on DP projections; extensor process‐to‐middle phalangeal condyle distance; and deep digital flexor tendon angle on LM projections. A matched pairs design and Student's t ‐test with a 95% confidence level were used to test for statistical significance. Compared to a bipodal stance, lateral DIPJ space width was significantly reduced on unipodal DP views, whereas mediolateral joint imbalance and to a lesser extent medial DIPJ space width were significantly increased. On unipodal LM views, there was a significant higher degree of DIPJ flexion. These findings suggest that stance should be carefully taken into consideration when measuring radiographic parameters in equine forefeet, especially if assessing foot balance and conformation, as unipodal stance significantly affects the mediolateral balance of the DIPJ on DP radiographs and significantly alters the phalangeal axis on LM radiographs.